Analysis of the Impact of the Application of the Team Game Tournament Cooperative Learning Model in PPKN Learning - Mahdania Citra Pradila; Mukhamad Murdiono (Journal Of Social Science (JoSS), 2025)
The background highlights observed issues in PPKn learning, where students perceive the subject as boring, leading to passive participation and unconducive classroom conditions. The purpose of writing this article is to identify the problems in Civics learning and to examine the impact of applying the Teams Game Tournament (TGT) cooperative learning model in Civics education. The method used in this research is descriptive qualitative with case study analysis, and data collection methods included observation, literature study, and visual analysis. The subjects of this research were students of class 7B at SMP Negeri 1 Mlati. The results showed that there was a problem in learning Civics subjects, namely that students were less active and considered Civics boring, with a lack of learning motivation. However, the application of the Teams Game Tournament (TGT) cooperative learning model in Civics learning made students more focused, active, varied, creative, and enthusiastic. The learning process became interactive, educational, fun, and conducive. Classroom conditions improved, and students were able to be responsible, cooperate, and compete fairly during the learning process. The implications suggest that innovative learning models like TGT can revitalize PPKn education by making it more student-centered and dynamic, aligning with national education goals.